2015
DOI: 10.1073/pnas.1515965112
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein dynamics in ion selectivity and allosteric coupling in the NaK channel

Abstract: Flux-dependent inactivation that arises from functional coupling between the inner gate and the selectivity filter is widespread in ion channels. The structural basis of this coupling has only been well characterized in KcsA. Here we present NMR data demonstrating structural and dynamic coupling between the selectivity filter and intracellular constriction point in the bacterial nonselective cation channel, NaK. This transmembrane allosteric communication must be structurally different from KcsA because the Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…A similar allosteric coupling pathway was also identified by the Henzler-Wildman laboratory in the nonselective cation channel NaK. There, they found that NaK exhibits long-range allostery through the selectivity filter and the channel scaffolding as a result of cation passage through the channel (73). Their findings, together with ours, suggest that this behavior may be a common feature within ion channels to tightly control channel function.…”
Section: Ssnmr Identifies Conformational Changes Upon Lipid Bindingsupporting
confidence: 83%
“…A similar allosteric coupling pathway was also identified by the Henzler-Wildman laboratory in the nonselective cation channel NaK. There, they found that NaK exhibits long-range allostery through the selectivity filter and the channel scaffolding as a result of cation passage through the channel (73). Their findings, together with ours, suggest that this behavior may be a common feature within ion channels to tightly control channel function.…”
Section: Ssnmr Identifies Conformational Changes Upon Lipid Bindingsupporting
confidence: 83%
“…Because computational models of channels are readily incorporated into multiscale cell and tissue models, 136,138 this approach could be used to identify how inactivation should be targeted therapeutically to stabilize excitation at the tissue level to prevent arrhythmia. As additional structural data emerges, including the Cryo-EM structure of a mammalian Na V channel, 139 conformational data from fluorescence experiments, 140 and even NMR data showing channel dynamics, 141 these models will only improve, provided that the computational approaches needed to incorporate this type of information into the models continue to be developed in parallel.…”
Section: Toward Molecularly Detailed Models Of Inactivationmentioning
confidence: 99%
“…These observations, together with mutagenesis studies on NaK, suggested that loss of contiguous binding sites (S1 and S2) is responsible for ion non-selectivity 13 , 14 . Moreover, no structural rearrangement was observed in the crystal structures of NaK with Na + , K + , or rubidium (Rb + ) and a single SF conformation was detected for NaK in bicelles at high temperature by solution-state NMR 15 . The different ions were therefore proposed to permeate through the same SF conformation with different preferential binding sites 11 , 16 .…”
Section: Introductionmentioning
confidence: 99%